2022
DOI: 10.1002/smll.202203331
|View full text |Cite
|
Sign up to set email alerts
|

Entrapped Molecule‐Like Europium‐Oxide Clusters in Zinc Oxide with Nearly Unaffected Host Structure

Abstract: Nanocrystalline ZnO sponges doped with 5 mol% EuO1.5 are obtained by heating metal–salt complex based precursor pastes at 200–900 °C for 3 min. X‐ray diffraction, transmission electron microscopy, and extended X‐ray absorption fine structure (EXAFS) show that phase separation into ZnO:Eu and c‐Eu2O3 takes place upon heating at 700 °C or higher. The unit cell of the clean oxide made at 600 °C shows only ≈0.4% volume increase versus undoped ZnO, and EXAFS shows a ZnO local structure that is little affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 95 publications
3
11
0
Order By: Relevance
“…10−20 nm) precipitate out of the ZnO lattice when annealed. 51 Our description of annealing-induced phase distribution in Ba−Zr−S thin films closely resembles the chemical inhomogeneity captured by STEM-EDS spectral imaging of the BZS-900 film, which clearly revealed areas of the film containing Zrand O-rich zones, which are Ba and S-deficient (ref 37, Figure 7). When BaZrS 3 crystallites grow in size with increasing annealing temperature, one expects ZrO 2 and other secondary oxide and sulfide phases to be redistributed more toward crystallite boundaries, which eventually emerge out of the film upon further annealing (1000 °C).…”
Section: ■ Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…10−20 nm) precipitate out of the ZnO lattice when annealed. 51 Our description of annealing-induced phase distribution in Ba−Zr−S thin films closely resembles the chemical inhomogeneity captured by STEM-EDS spectral imaging of the BZS-900 film, which clearly revealed areas of the film containing Zrand O-rich zones, which are Ba and S-deficient (ref 37, Figure 7). When BaZrS 3 crystallites grow in size with increasing annealing temperature, one expects ZrO 2 and other secondary oxide and sulfide phases to be redistributed more toward crystallite boundaries, which eventually emerge out of the film upon further annealing (1000 °C).…”
Section: ■ Discussionsupporting
confidence: 69%
“…Similar observations were made in Eu doping in ZnO nanosponges, where molecular Eu–O clusters embedded in hexagonal ZnO crystallites of similar dimensions (ca. 10–20 nm) precipitate out of the ZnO lattice when annealed …”
Section: Discussionmentioning
confidence: 99%
“…EXAFS and DFT modelling suggested that (EuO1.5)4-8 clusters were present inside the ZnO crystals, in excellent agreement with the experimental data. 22 This surprising finding explained how large amount of Eu-ions can be incorporated into ZnO without much change of XRD unit cell-parameters. With such high Eu-loading there should only be less than ca.…”
mentioning
confidence: 94%
“…These sponges showed XRD patterns completely assignable to h-ZnO with very minor changes in unit cell-parameters. 22 However, TEM, XPS, TGA and IR spectroscopy showed the presence of minor amounts of organic residues which were replaced by Eu-oxo-carbonate when heating at 300 -500 o C for 3 minutes. Heating at 600 o C for 3 min.…”
mentioning
confidence: 97%
See 1 more Smart Citation